Relationship Between ChatGPT Use and Critical Thinking in Organic Chemistry Learning - Fikriya, Sakti Hidayati; Zulqurnain, Muhammad; Suharman, Andi; Ad’hiya, Eka (Pendidikan Kimia FKIP Universitas Jambi, 2026)
This study explored the relationship between ChatGPT use and critical thinking skills in Organic Chemistry learning among chemistry education students. A quantitative correlational research design was employed involving 87 undergraduate students enrolled in an Organic Chemistry course at Sriwijaya University. Data on ChatGPT use were collected through a four-point Likert-scale questionnaire covering frequency of use, perceived usefulness, ease of use, and ethical awareness, while critical thinking skills were assessed using a three-component test consisting of answer accuracy, scientific reasoning, and self-reported confidence level. Data were analyzed using descriptive statistics and Pearson correlation analysis. The findings revealed that most students frequently used ChatGPT to support their understanding of complex Organic Chemistry concepts and perceived it as helpful for improving learning efficiency. However, the Pearson correlation analysis showed no significant relationship between ChatGPT use and students’ critical thinking skills (r = −0.060, p = 0.581). The findings suggest that the ChatGPT use alone does not automatically enhance or diminish critical thinking skills. Its educational impact depends on how students critically evaluate, verify, and utilize AI-generated information. Therefore, pedagogical guidance is necessary to support the meaningful integration of AI-assisted learning in Organic Chemistry education.